2013
DOI: 10.1093/humrep/det396
|View full text |Cite
|
Sign up to set email alerts
|

Is ovarian hyperstimulation associated with higher blood pressure in 4-year-old IVF offspring? Part I: multivariable regression analysis

Abstract: The authors have no conflicts of interest to declare. The study was supported by the University Medical Center Groningen, the Cornelia Foundation and the school for Behavioral- and Cognitive Neurosciences. The sponsors of the study had no role in study design, data collection, data analysis, data interpretation or writing of the report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 31 publications
3
24
1
2
Order By: Relevance
“…Effects observed in IVP produced adult mice born include increased blood pressure associated with increased enzymatic activities of angiotensin‐converting enzyme in the serum and hepatic phosphoenolpyruvate carboxykinase in the liver in female offspring at 27 weeks (Watkins et al, ). Interestingly, similar observations were made in humans where ovarian hyperstimulation has been associated with higher blood pressure in 4 year old IVF children (Seggers et al, ). Altered liver phospholipid profiles linked to atherosclerosis and diabetes were also observed in CD1 adult mice born after IVP using KSOM AA (Li, Xiao, et al, ).…”
Section: Long‐term Effects Of Artsupporting
confidence: 68%
“…Effects observed in IVP produced adult mice born include increased blood pressure associated with increased enzymatic activities of angiotensin‐converting enzyme in the serum and hepatic phosphoenolpyruvate carboxykinase in the liver in female offspring at 27 weeks (Watkins et al, ). Interestingly, similar observations were made in humans where ovarian hyperstimulation has been associated with higher blood pressure in 4 year old IVF children (Seggers et al, ). Altered liver phospholipid profiles linked to atherosclerosis and diabetes were also observed in CD1 adult mice born after IVP using KSOM AA (Li, Xiao, et al, ).…”
Section: Long‐term Effects Of Artsupporting
confidence: 68%
“…Various studies have shown that children born after ART have poorer metabolic and vascular profiles than naturally conceived children, with elevated systolic and diastolic blood pressures, higher fasting glucose levels, increased central adiposity and vascular dysfunction with pulmonary hypertension . According to those authors, the changes mentioned seems to be independent of prematurity, birthweight and parental characteristics, suggesting that features related to ART could directly contribute to these adverse health effects …”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have demonstrated that there were higher risks of birth defects and imprinted diseases in ART offspring [9][10][11]. A recent report showed that COH could lead to higher systolic blood pressure percentiles in 4-year-old children born following in vitro fertilization and embryo transfer (IVF-ET) [12]. Therefore, it is possible that COH might result in long-term impairments to the offspring, but the underlying mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%